Avantajele competitive ale României pe piaţa internă a UE - Geomina Țurlea; Valentin Cojanu; Alina Alexoaei; Georgiana Neculau; Ioan-Radu Petrariu (European Institute of Romania, 2014)
– This study contributes to the literature on the competitiveness of Romanian exports with a new perspective over the decade 2001-2011, by overlapping of two complementary analyses: of the export performance dynamics and of the domestic revenues created by export manufacturers and their suppliers. The analyzed period includes the period of global economic growth (mainly 2003-2007) and the first years of the economic crisis (2009-2011 ). The year 2007, when Romania joined the European Union, is in the middle of the analyzed period. The dynamics of Romania's export performance was assessed through a specific method combining three different research lines(1) changes in the ranking of exported products in the reference years 2001 and 2011, (2) evolution of the performance of key products exported in 2001 and (3) the position in 2001 of key products exported in 2011. The analysis of domestic revenues created by export manufacturers and their suppliers provides, for the first time for Romania a brief study on the position of the country on the global value chain, following the logic proposed by the European Commission in its last two European Competitiveness Reports (2012 and 2013). When corroborated, the results of the two analyses can be used to discuss the extent to which the current structure of exports contributes to the generation of domestic revenues and as such might prove useful in the debate on the identification of a country brand for Romania. In order to achieve the latter goal, we conducted two detailed case studies on two reference sectors of the Romanian economy: motor vehicles and creative industries. [...]
Keywords: 330; Export; Performance-Messung; Einnahmen; Internationaler Wettbewerb; EU-Binnenmarkt; Rumänien